PERENCANAAN PLTS SEBAGAI CATU DAYA PADA POMPA AIR SHIMIZU PS-128 BIT - Tharo, Zuraidah; Hamdani, Hamdani; Andriana, Melly; Kusuma, Budhi Santri (Seminar Nasional Sosial Sains dan Teknologi Halal; 2021, 2022)
Renewable Energy is New Renewable Energy which is currently being suggested for its use from both local and global governments. Apart from being used as primary energy for power generation, NRE is also being developed as energy that is used directly by the user sector. Solar Power Center (PLTS) is one form of Renewable Energy, namely an electric center that converts sunlight into electrical energy. PLTS is often also called Solar Cell or Solar Energy. The simple concept of converting sunlight into electrical energy makes PLTS more widely used than other renewable energies. Utilization of sunlight has begun to be widely used in various purposes, in this case the use of sunlight is planned as a power supply for the Shimizu PS-128 BIT Water Pump engine. Planning begins by calculating how much power the machine needs to pump water from the well, then calculating the need for how much Solar Panel (PhotoVoltaic) is needed and adjusting to the size of the inverter and battery to be used.